An Analysis of Maternal Death’ Cause in Bandung City (Epidemiology Study in Efforts to Lower Maternal Mortality Rate in West Java Province) - Hartinah Hartinah; Innama Sakinah; Tita Husnitawati Madjid; Hadi Susiarno; Sukandar Hadyana; Agnes Dwi H; Herry Herman (Universitas STRADA Indonesia, 2020)
The results showed that the factors associated with maternal mortality based on the analysis were history of ANC (OR = 37.4; 95% CI: 9.5 - 313.6; p = 0.012), place of death (OR = 21.5; 95% CI: 2.5 - 188.5; p = 0.001), Health Facility (OR = 21.5; 95% CI: 2.5 - 188.5; p = 0.001), Non-referral case (OR = 91.2; 95% CI: 11.1 - 750; p = 0.001), delay in referral (OR = 122.1; 95% CI: 14.7 - 1010.2; p = 0.001). The results of the qualitative study showed that maternal mortality was affected by several factors, such as the low level of understanding of danger signs in pregnancy, labor and childbirth, low levels of late referral by overdue family decisions.